OPTIMALISASI PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) MELALUI APLIKASI SISTEM INFORMASI MANAJEMEN DANA BOS (SIMBOS) DI KABUPATEN BANGKA TENGAH - Octabella , Herliza; Haromin; Helwani; Riswati (Prodi Ilmu Pemerintahan FISIP UNIBBA, 2025)
The problem that motivates researchers to take this title is how to optimize the management of school operational assistance funds (BOS) through the application of the bos fund management information system (SIMBOS) in Central Bangka Regency. to determine and analyze the optimization of the management of school operational assistance funds (BOS) through the application of the boss fund management information system (SIMBOS) in Central Bangka Regency. This study uses a descriptive qualitative research method with an inductive approach, which allows in-depth exploration of the phenomenon under study. Data collection relied on in-depth interview techniques with various stakeholders related to the management of BOS funds, as well as documentation studies of various official documents, financial reports, and relevant regulations. The findings obtained were that the application of the SIMBOS application in the management of BOS funds in Kabupaten Bangka Tengah covered various crucial stages, starting from planning, organizing, directing, coordinating, monitoring, and reporting, which overall became more integrated and transparent. Nevertheless, this study also identified several obstacles that need serious attention, such as the limited capacity of human resources in some education units to understand and operate the SIMBOS application effectively, as well as the lack of adequate supporting infrastructure. Based on the results of the research and analysis, it can be concluded that the use of SIMBOS has great potential to optimize the management of BOS funds, minimize the risk of budget misuse, and strengthen the accountability of education financial management in Central Bangka District.